Subpolar Gyre Variability, Cruise No. MSM53, March 31 - May 09, 2016, Kiel (Germany) - St. John's (Canada) - Kieke, Dagmar; Böke, Wolfgang; Büttner, Sharina; Bulsiewicz, Klaus; Danek, Christopher; Hempel, Tim; Khordakova, Dina; Mirau, Bastian; Rochner, Andrea; Roessler, Achim; Rohlfs, Nina; Schneehorst, Anja; et al. (DFG-Senatskommission für Ozeanographie, 2018)
Cruise MSM53 with RV MARIA S. MERIAN dealt with investigating the strength and intra- to interannual variability of the oceanic circulation system and water mass structure in the southern subpolar North Atlantic, as well as the export of subpolar water masses from and import of sutropical water masses to the North Atlantic. : MARIA S. MERIAN-Berichte